Strengthening community social capital to increase tourism in Burai Tourism Village, Ogan Ilir - Eva Lidya; Yulasteriyani Yulasteriyani; Yunindyawati Yunindyawati; Yusnaini Yusnaini (Community Empowerment, 2022)
The purpose of this community service is to assist the Burai tourist village in achieving its goal of being a tourist destination in Ogan Ilir Regency, South Sumatra. The method is preparation (pre-test and MSME materials, as well as the importance of social capital) is followed by counseling and evaluation (post-test). The success of this program may be determined by two factors: 1) the program went off without a hitch; and 2) the material was well received and comprehended by the participants. The evaluation results reveal that the community is motivated to use its social capital to develop tourist potential in Burai Village.